Loss of beef during primary production at Swedish farms 2002–2021 - Strid, Ingrid; Jacobsen, Maria; Alvåsen, Karin; Rydén, Jesper (Frontiers in Sustainable Food Systems, 2023)
Loss of animals is a considerable waste of resources in the meat supply chain, where quantitative data are scarce but critical for guiding improvements. In this study, we used material flow analysis to track the amount of beef diverted away from the food supply chain at the farm level. The beef losses (absolute and as the proportion of yearly initial production) were estimated from data on assisted and unassisted deaths of cattle on Swedish farms obtained from the central register of bovine animals for 2002–2021 combined with official statistics on slaughter weight. The fallen animals were grouped according to age, sex and breed, to enable estimations of the lost amount of carcass weight, both in total and per animal group. The yearly loss during primary production 2017–2021 was on average 13,000 ton carcass weight, or 8.5% of the initial production. No decreasing trend for the loss rate could be determined after 2015, when the Agenda 2030 target 12.3 (Halved food waste and reduced early losses) was introduced. Female dairy breeds showed greater beef losses than dairy males or beef breeds and crossbreeds of both sexes, and their beef losses mostly occurred at 4–5 years of age, thus constituting the hot spot group for lost beef. The results can serve as a base for directed reduction efforts.